Occupational Prenatal Radiation Exposure and Occupational Safety: Position Paper for Pregnant and breastfeeding Personnel in Interventional Procedures with Ionizing Radiation Berufliche pränatale Strahlenexposition und Berufssicherheit: Positionspapier für schwangeres und stillendes Personal bei interventionellen Verfahren mit ionisierender Strahlung - Becker, Lena Sophie; Stein, Thomas; Frisch, Anne; Dewald, Cornelia Lieselotte Angelika; Blum, Sophia Freya Ulrike; Wintergerst, Charlotte; Torsello, Giovanni; Peperhove, Matti Jonas; Pöhler, Gesa; Staudacher, Emona; Franke, Mareike; Tritt, Stephanie; et al. (Röfo: Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2025)
Background The increasing number of women working in medical surgical professions involving ionizing radiation creates new challenges for the safety of both pregnant and breastfeeding employees and the management of prenatal radiation exposure. The aim of this manuscript is to discuss the biological effects of loosely-ionizing radiation, evaluate the associated risks, and discuss the principles of German radiation protection law in the context of pregnancy and breastfeeding. Method To assess the effects of prenatal radiation exposure, we reviewed relevant sources such as reports from the German Commission on Radiological Protection, United Nations Scientific Commission on Effects of Atomic Radiation (UNSCEAR), and publications from the International Commission on Radiological Protection (ICRP). Additionally, the current German legislation, with focus on radiation protection and maternity protection laws, was outlined in context. Conclusion The analysis shows that adhering to regulatory dose limits minimizes the risks of pregnancy complications, congenital malformations, developmental delays, mutagenic and carcinogenic effects. Special attention is required during the first trimester, in which radiation sensitivity is highest. Adherence to legal framework and associated protective measures in Germany provides under certain conditions a safe working environment for pregnant and breastfeeding women in surgical professions that involve ionizing radiation.
CRIS-Team Scopus Importer:2025-04-11
Keywords: interventional procedures; pregnancy; radiation safety